Scanning Probe Microscopy in Nanoscience and Nanotechnology - Bhushan, Bharat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents the physical and technical foundation of the state of the art in applied scanning probe techniques. It constitutes a timely and comprehensive overview of SPM applications. The chapters in this volume relate to scanning probe microscopy techniques, characterization of various materials and structures and typical industrial applications, including topographic and dynamical surface studies of thin-film semiconductors, polymers, paper, ceramics, and magnetic and biological materials. The chapters are written by leading researchers and application scientists from all over the world and from various industries to provide a broader perspective. With a foreword by the co-inventor of AFM, Christoph Gerber
Scanning Probe Microscopy Techniques -- Dynamic Force Microscopy and Spectroscopy Using the Frequency-Modulation Technique in Air and Liquids -- Photonic Force Microscopy: From Femtonewton Force Sensing to Ultra-Sensitive Spectroscopy -- Polarization-Sensitive Tip-Enhanced Raman Scattering -- Electrostatic Force Microscopy and Kelvin Force Microscopy as a Probe of the Electrostatic and Electronic Properties of Carbon Nanotubes -- Carbon Nanotube Atomic Force Microscopy with Applications to Biology and Electronics -- Novel Strategies to Probe the Fluid Properties and Revealing its Hidden Elasticity -- Combining Atomic Force Microscopy and Depth-Sensing Instruments for the Nanometer-Scale Mechanical Characterization of Soft Matter -- Static and Dynamic Structural Modeling Analysis of Atomic Force Microscope -- Experimental Methods for the Calibration of Lateral Forces in Atomic Force Microscopy -- Characterization -- Simultaneous Topography and Recognition Imaging -- Structural and Mechanical Mechanisms of Ocular Tissues Probed by AFM -- Force-Extension and Force-Clamp AFM Spectroscopies in Investigating Mechanochemical Reactions and Mechanical Properties of Single Biomolecules -- Multilevel Experimental and Modelling Techniques for Bioartificial Scaffolds and Matrices -- Quantized Mechanics of Nanotubes and Bundles -- Spin and Charge Pairing Instabilities in Nanoclusters and Nanomaterials -- Mechanical Properties of One-Dimensional Nanostructures -- Colossal Permittivity in Advanced Functional Heterogeneous Materials: The Relevance of the Local Measurements at Submicron Scale -- Controlling Wear on Nanoscale -- Contact Potential Difference Techniques as Probing Tools in Tribology and Surface Mapping -- Industrial Applications -- Modern Atomic Force Microscopy and Its Application to the Study of Genome Architecture -- Near-Field Optical Litography -- A New AFM-Based Lithography Method: Thermochemical Nanolithography -- Scanning Probe Alloying Nanolithography -- Structuring the Surface of Crystallizable Polymers with an AFM Tip -- Application of Contact Mode AFM to Manufacturing Processes -- Scanning Probe Microscopy as a Tool Applied to Agriculture.
Keywords: Materials; Engineering; Nanotechnology; Material Science; Nanotechnology; Condensed Matter Physics; Engineering, general